2008
DOI: 10.1007/s10158-008-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Engrailed expression in subsets of adult Drosophila sensory neurons: an enhancer-trap study

Abstract: Engrailed (En) has an important role in neuronal development in vertebrates and invertebrates. In adult Drosophila, although En expression persists throughout adulthood, a detailed description of its expression in sensory neurons has not been made. In this study, en-GAL4 was used to drive UAS-CD8::GFP expression and the projections of sensory neurons were examined with confocal microscopy. En protein expression was confirmed using immunocytochemistry. In the antenna, En is present in subsets of Johnston's orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
(94 reference statements)
2
8
0
Order By: Relevance
“…There are approximately 89±6 (N = 5) en-GAL4 -expressing neurons in total. As shown previously [24], and confirmed here, all such neurons contain some immunoreactivity for the Engrailed and Invected proteins, although there is not necessarily a correlation between the intensity of antibody staining and that of CD8::GFP fluorescence. It is therefore reasonable to conclude that the e16E insertion faithfully reports the expression of the engrailed gene.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…There are approximately 89±6 (N = 5) en-GAL4 -expressing neurons in total. As shown previously [24], and confirmed here, all such neurons contain some immunoreactivity for the Engrailed and Invected proteins, although there is not necessarily a correlation between the intensity of antibody staining and that of CD8::GFP fluorescence. It is therefore reasonable to conclude that the e16E insertion faithfully reports the expression of the engrailed gene.…”
Section: Resultssupporting
confidence: 85%
“…The GAL4 enhancer trap line en-GAL4 e16E was used to drive CD8::GFP expression in en -expressing JONs [24]. As shown previously, these neurons lie predominantly in the ventral-most half of the posterior group of receptors (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although progenitors of hair cells and support cells express sox2 , knockdown studies showed no effect on hair cell formation but an effect on maintenance of hair cells and support cells (Millimaki et al, 2010). In Drosophila , expression of engrailed (Blagburn, 2008) in mature olfactory sensory neurons suggests additional functions in maintenance rather than in early development. Taken together, transcription factors previously known for functions during early development are now known to have additional roles in later stages, and splash may be another example.…”
Section: Discussionmentioning
confidence: 99%